2019
DOI: 10.1093/cdn/nzz082
|View full text |Cite
|
Sign up to set email alerts
|

A Nutrigenomics Approach Using RNA Sequencing Technology to Study Nutrient–Gene Interactions in Agricultural Animals

Abstract: Thorough understanding of animal gene expression driven by dietary nutrients can be regarded as a bottom line of advanced animal nutrition research. Nutrigenomics (including transcriptomics) studies the effects of dietary nutrients on cellular gene expression and, ultimately, phenotypic changes in living organisms. Transcriptomics can be applied to investigate animal tissue transcriptomes at a defined nutritional state, which can provide a holistic view of intracellular RNA expression. As a novel transcriptomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 124 publications
0
11
0
1
Order By: Relevance
“…Among the transcriptomic approaches, RNA-sequencing (RNA-seq) simultaneously measures the differential expression of thousands of genes in any biological matrix. The resulting information can be used to determine the effects of a certain condition (e.g., a supplemented diet) from the perspective of the biological processes or molecular functions involved rather than from the expression levels of individual genes [2].…”
Section: Introductionmentioning
confidence: 99%
“…Among the transcriptomic approaches, RNA-sequencing (RNA-seq) simultaneously measures the differential expression of thousands of genes in any biological matrix. The resulting information can be used to determine the effects of a certain condition (e.g., a supplemented diet) from the perspective of the biological processes or molecular functions involved rather than from the expression levels of individual genes [2].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, quantitative trait loci have been identified to accelerate the genetic control of economically important traits by means of various candidate genes, such as the ryanodine receptor ( RYR1 ), protein kinase AMP -activated non-catalytic subunit gamma 3 ( PRKAG3 ), fatty acid-binding protein 3 ( HFABP ), and melanocortin 4 receptor ( MC4R ) [ 9 , 10 ]. Recently, studies have investigated the transcript abundance of a group of candidate genes involved in metabolism, nutrient metabolites, and muscle structural genes [ 4 , 7 , 8 , 11 , 12 , 13 , 14 ]. These studies identified key regulatory genes that are significantly associated with pork quality and muscle characteristics in purebred pigs.…”
Section: Introductionmentioning
confidence: 99%
“…RNA-Seq is used as a powerful approach for the identification of differential expression in response to specific nutrients and diets, compelling physiological conditions, such as disease, energy restriction, and vitamin and mineral deficiency in an organism. Recovering such an exclusively big data from RNA-Seq analysis provides robust and accurate information for animal nutritionists and eventually allows rations to be modified or personalized in order to improve objective traits of ruminants (Hasan et al, 2019). Quantitative Polymerase Chain Reaction (i.e., Real-Time PCR/qPCR) is a PCR-based technology that allows the validation of a small set of differentially expressed genes, usually recovered from large microarray or RNA-Seq studies.…”
Section: Techniques and Technologies Used For Nutrigenomics Researchmentioning
confidence: 99%